Resilience Evaluation in the Montes De María Beekeeping Chain as a Tool to Improve Safety and Sustainability in the Colombian Caribbean Region - Jalelys Liceth Leones-Cerpa; Rosalba Cabrera; Camila Madero; Juan F. Restrepo; Katherine Velandia; Eduardo Sanchez-Tuiran; Karina A. Ojeda Delgado (Chemical Engineering Transactions)
Beekeeping is an important economic activity in the Colombian Caribbean, but its sustainability and resilience face significant challenges. This study assesses the resilience of the Montes de María beekeeping chain through ecosystem characterization based on GLOBE protocols and theoretical risk identification. Surveys were conducted with beekeepers to assess their exposure to different risks, including environmental, socio-cultural, economic and physical factors, as well as bee aggressiveness. Resilience was analyzed using four components, each with specific indicators, which were consolidated into a Resilience Index (RI). Results indicate that the socio-cultural component has the greatest impact on resilience, influenced by limited government support and community awareness of bees. The promotion of beekeeping products, the promotion of teamwork ergonomics, and the establishment of robust regulations for beekeeping practices and products are critical steps in improving the resilience and competitiveness of the sector.